Drone Berbahan Komposit Serat Rami Dengan Karbon Aktif-Barium M-Heksaferit Sebagai Radar Absorbing Material - Aritonang, Sovian; Hijrianisa, Alya; Pratita, Elda; Ningrum, Hanifa Setya; Pangestu, Bintang Brilliant (Rekayasa Material, Manufaktur dan Energi, 2024)
Radar is a crucial tool in military applications for detecting enemy objects in its vicinity, but its presence can pose a risk of being detected by adversaries. Therefore, this research focuses on the development of Radar Absorbing Material (RAM) using activated carbon obtained from cassava peel and Barium M-Hexaferrite. The research results indicate that this combination can be used as a protective layer on military drones made of composite hemp fibers, enhancing the drone's ability to absorb radar waves, thus reducing the risk of detection by adversaries. This improves the effectiveness of military operations and contributes to environmental preservation through the use of eco-friendly materials.